2011
DOI: 10.1089/hum.2010.164
|View full text |Cite
|
Sign up to set email alerts
|

Adeno-Associated Virus Serotype 8 Gene Transfer Rescues a Neonatal Lethal Murine Model of Propionic Acidemia

Abstract: Propionic acidemia (PA) is an autosomal recessive disorder of metabolism caused by a deficiency of propionylcoenzyme A carboxylase (PCC). Despite optimal dietary and cofactor therapy, PA patients still suffer from lethal metabolic instability and experience multisystemic complications. A murine model of PA (Pcca -/-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 21 publications
3
50
0
Order By: Relevance
“…However, these studies demonstrated efficacy only at early time points. 22,29,30 This work supports the ability of single AAV treatment to mitigate some PA phenotypes over the lifespan of mice.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…However, these studies demonstrated efficacy only at early time points. 22,29,30 This work supports the ability of single AAV treatment to mitigate some PA phenotypes over the lifespan of mice.…”
Section: Discussionsupporting
confidence: 67%
“…22,29,30 To determine if single intravenous AAV treatment could mediate long-lasting metabolite correction, propionylcarnitine and MeCit levels were monitored in male and female mice over 1.5 years after injection (Fig. 4).…”
Section: Long-term Biochemical Effects Of Single Aav8-pccaco Therapymentioning
confidence: 99%
“…Nonintegrating vectors based on adenovirus or adenoassociated virus (AAV) have shown high transduction efficiency in neonatal gene transfer; however, both vector systems suffer significant loss of transgene expression because of dilution of vector genome during rapid cell proliferation, especially in liver (Wang et al, 2005;Cunningham et al, 2008;Hu et al, 2011). Despite the reduction of transgene expression levels and vector genome copies, therapeutic effects or long-term rescue of neonatal lethality have been demonstrated in several animal models (Daly et al, 2001;CarrilloCarrasco et al, 2010;Chandler and Venditti, 2010;Yiu et al, 2010;Chandler et al, 2011;Cotugno et al, 2011;Hu et al, 2011). In these cases, expression of the normal gene in a small percentage of stably transduced cells accounts for the clinical effects.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work and the work of others showed that treatment of PA mice with liver-biased AAV8 and Ad5 vectors is able to significantly reduce systemic PA metabolites (Chandler et al, 2011;Guenzel et al, 2013). However, liver-biased vectors are not absolutely liver specific, and so they may also deliver the PCCA protein to additional nonhepatic cells (Fig.…”
Section: Discussionmentioning
confidence: 94%